1995
DOI: 10.1159/000134034
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome painting analysis of early oogenesis in human trisomy 18

Abstract: We have used chromosome 18-specific painting probes to analyze early stages of oogenesis in two human trisomy 18 fetuses. At leptotene, a diffuse, nonlinear chromosomal fluorescence was detected as one (27%), two (42%), or three (31 %) signals in 534 cells. The variation in size of these signals implies the possibility of associations between homologs prior to zygotene. At pachytene, about 75 % (339/453) of the cells had a trivalent configuration, and almost half of these cells exhibited almost complete triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
4
23
0
Order By: Relevance
“…In summary, we conclude that the present study agrees with previous studies performed in euploid oocytes in which a high pairing process efficiency was described (Cheng & Gartler 1994, Cheng et al 1995, Roig et al 2005a. Our study presents the first analysis of the pairing process for chromosome 13 in oocytes from fetuses with trisomy 13.…”
Section: Trivalent Efficiencysupporting
confidence: 92%
See 3 more Smart Citations
“…In summary, we conclude that the present study agrees with previous studies performed in euploid oocytes in which a high pairing process efficiency was described (Cheng & Gartler 1994, Cheng et al 1995, Roig et al 2005a. Our study presents the first analysis of the pairing process for chromosome 13 in oocytes from fetuses with trisomy 13.…”
Section: Trivalent Efficiencysupporting
confidence: 92%
“…As has been reported in earlier studies (Cheng et al 1995, 1998, Roig et al 2005a, 2005b for chromosomes 13, 18, and 21, we have observed that pairing of the 21 and X homologues starts during the late leptotene stage. Since the first piece of evidence of telomeric clustering has been detected during the leptotene/zygotene transition in human oocytes (Roig et al 2004(Roig et al , 2005b, as was already proposed in humans (Bojko 1983) and demonstrated in other species (Scherthan 2003), these results seem to support the hypothesis that bouquet topology promotes homologue encounter and facilitates the synaptic process during meiotic prophase.…”
Section: Homologue Pairing Process In Euploid Fetusessupporting
confidence: 90%
See 2 more Smart Citations
“…The meiotic division is blocked until the female enters puberty. Despite the difficulties associated with the study of human female meiotic prophase, some aneuploid ovaries have been studied using classical staining techniques (Luciani et al 1976, Wallace & Hulten 1983, Speed 1984, fluorescent in situ hybridization (FISH) (Cheng et al 1995(Cheng et al , 1998 or immunofluorescent (IF) (Barlow et al 2002) techniques.…”
Section: Introductionmentioning
confidence: 99%